Al-loaded core-shell structure calcium-based heat storage particle and preparation method thereof

By constructing a hydrophobic surface of manganese dioxide and graphite on the outer surface of the calcium-based heat storage material particles, forming an Al-loaded putaway structure, the problem of low absorbance of calcium-based heat storage material is solved, and efficient utilization of solar radiation energy and maintaining high storage is achieved. Energy density effect.

CN119432333AActive Publication Date: 2025-02-14NANJING NORMAL UNIVERSITY

Patent Information

Application Number
CN202411567881.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Due to the low absorbance of calcium-based heat storage materials, solar radiation energy cannot be effectively utilized in solar power generation, and doped absorbing components will consume active CaO and reduce heat storage density.

Method used

Al-loaded putaway structure calcium-based heat storage particles are used to construct the hydrophobic surface of manganese dioxide and graphite on the outer surface of the particles, forming a "black and white outside" structure to improve light absorption performance, while maintaining the amount of internal active CaO to ensure storage Heat density.

Benefits of technology

Without consuming internal active CaO, the absorbance of calcium-based heat storage materials is improved, its ability to utilize solar radiation, improve solar energy utilization, and maintain high energy storage density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432333A_ABST
    Figure CN119432333A_ABST
Patent Text Reader

Abstract

The invention discloses an Al-loaded core-shell structure calcium-based heat storage particle and a preparation method thereof, and belongs to the technical field of heat storage materials. Manganese dioxide amp is adopted; a calcium-based raw material is calcium hydroxide which is low in price and easy to obtain, and inert carrier aluminum nitrate with different proportions is doped in the calcium hydroxide; by changing the mass ratio of manganese dioxide to graphite in the hydrophobic surface, the absorbance of the calcium-based heat storage material with the core-shell structure is regulated and controlled, and the defect that a traditional calcium-based material is poor in light absorption performance is overcome; the inert carrier is doped in different proportions, so that the heat storage / release performance of the calcium-based material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of heat storage materials, and in particular relates to Al-loaded core-shell structure calcium-based heat storage particles and a preparation method thereof. Background Art

[0002] Faced with energy shortages and environmental problems, the large-scale use of clean energy has become an energy development trend. Concentrated solar power generation (CSP), as one of the main ways to utilize solar energy, provides an effective solution to the global energy crisis. Thermal energy storage technology can solve the intermittent and instability of concentrated solar power generation. Compared with sensible heat storage and latent heat storage, thermochemical energy storage (TCES) has high energy storage density, small energy loss and long cycle, and has broad application prospects.

[0003] At present, among different TCES technologies, calcium cycle (CaL) energy storage technology has attracted widespread attention due to its wide source, non-toxic and environmentally friendly advantages. Calcium carbonate stands out among many thermochemical energy storage materials, with its industrial advantages of low cost, easy availability and high reaction kinetics. Poor light absorption characteristics are one of the main reasons why calcium-based thermal storage materials have not been applied on a large scale.

[0004] Currently in the field of thermochemical heat storage, scholars are more concerned about the storage / release stability of calcium during the calcium cycle. By adding inert carriers and pore-forming agents to modify calcium-based materials, calcium-based heat storage materials are formed and granulated to reduce the precipitation during the cycle, and many phased results have been achieved. In view of the low solar radiation absorption rate of calcium-based materials, uniform doping of light-absorbing components can effectively improve the light absorption performance. However, the increase in the absorbance of calcium-based heat storage materials comes at the expense of the active CaO required for the reaction, and the reduction in active components means a decrease in heat storage density. So far, few scholars have proposed effective solutions to this problem. Summary of the invention

[0005] To solve the above problems, the present invention discloses an Al-loaded core-shell calcium-based heat storage particle based on hydrophobic surface construction and a preparation method thereof, including the ratio of manganese dioxide and graphite, the content ratio of active CaO and inert carrier, and a molding and granulation method.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] The present invention provides an Al-loaded core-shell structure calcium-based heat storage material, which is "black outside and white inside": manganese and its oxide form a dark outer shell to absorb light, and the inside is an aluminum-loaded calcium-based material for heat storage / release reaction. The calcium-based material is calcium hydroxide, Al(NO3)3·9H2O is an inert load, and the light-absorbing component is manganese and its oxide.

[0008] Furthermore, the hydrophobic surface components required for the preparation of the Al-loaded core-shell structure calcium-based heat storage material are manganese dioxide and graphite, and the mass ratio of manganese dioxide to graphite in the hydrophobic surface is 1:0-4. Preferably, the mass ratio of manganese dioxide to graphite in the hydrophobic surface is 1:0, 3:2, 1:2 or 1:4;

[0009] The calcium-based material includes CaO and Ca 12 Al 14 O 33 The content of CaO in the calcium-based material is 92.5%-80%, Ca 12 Al 14 O 33 The content of CaO and Ca in the calcium-based material is 7.5%-20%; preferably, 12 Al 14 O 33 The contents are 92.5% and 7.5%, 84.5% and 15.5% or 80% and 20% respectively.

[0010] The present invention also provides a method for preparing an Al-loaded core-shell calcium-based heat storage material, comprising the following steps:

[0011] Step 1, using manganese dioxide and graphite to prepare a hydrophobic surface and placing it at an angle;

[0012] Step 2, mixing deionized water, calcium hydroxide and aluminum nitrate, and stirring to form a uniform wet mixture;

[0013] Step 3, the wet mixture obtained in step 2 is titrated on an inclined hydrophobic surface through a capillary and syringe combination tool to obtain wet Al-loaded core-shell calcium-based heat storage particles with uniform particle size;

[0014] Step 4, drying the wet Al-loaded core-shell structured calcium-based heat storage particles obtained in step 3;

[0015] Step 5, calcining the particles obtained in step 4 to obtain the Al-loaded core-shell structured calcium-based heat storage particles.

[0016] Further, in step 1, the mass ratio of manganese dioxide to graphite is 1:0.6-4. Preferably, the mass ratio of manganese dioxide to graphite is 3:2-1:4, and more preferably, the mass ratio of manganese dioxide to graphite is 3:2, 1:2 or 1:4.

[0017] Furthermore, in step 2, the mass ratio of the calcium hydroxide to aluminum nitrate is 2.5-9:1; and the mass volume ratio of the total mass of the calcium hydroxide and aluminum nitrate to deionized water is 3-3.1:5.

[0018] Furthermore, in step 4, the drying temperature is 65-85° C., and the drying time is 12-14 hours.

[0019] Furthermore, in step 5, the calcination conditions are: heating to 900°C at a heating rate of 10°C / min and maintaining the temperature for 90 minutes. Calcination removes the stable substance Ca generated by graphite 12 Al 14 O 33 .

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention uses a manganese dioxide & graphite mixed component hydrophobic surface to assist in constructing Al-loaded core-shell structure calcium-based heat storage particles, so that the calcium-based heat storage material can achieve high absorbance characteristics without consuming internal active CaO.

[0022] (2) The present invention not only realizes the transformation of calcium-based materials from white to black by placing light-absorbing components on the outer surface of the particles, but also solves the problem of consuming active CaO by doping with light-absorbing components. This "black outside and white inside" core-shell structure calcium-based heat storage particle is used in a thermochemical heat storage system, which can efficiently utilize solar radiation energy and has a high energy storage density, thereby improving the utilization rate of solar energy.

[0023] (3) The present invention controls the absorbance of the core-shell structure calcium-based heat storage material by changing the mass ratio of manganese dioxide and graphite in the hydrophobic surface, thereby overcoming the disadvantage of poor light absorption performance of traditional calcium-based materials; its calcium-based raw material is cheap and readily available calcium hydroxide, which is doped with different proportions of inert carrier aluminum nitrate. By doping with different proportions of inert carriers, the heat storage / release performance of the calcium-based material is enhanced.

[0024] (4) The raw materials required for the heat storage material of the present invention are cheap and easily available, the operation steps are simple, and no high temperature or chemical toxicity reactions are involved, which is suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the spectral absorbance of Comparative Example 1 and Examples 1 to 3;

[0026] Figure 2 The energy storage density calculated based on CaO for Comparative Example 2 and Examples 3 to 5;

[0027] Figure 3 Schematic diagram of the structure of the capillary and syringe combination tool. DETAILED DESCRIPTION

[0028] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0029] If no specific conditions or conditions are specified in the examples, the methods or conditions described in the literature in the art are followed according to the instructions. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased on the market.

[0030] The capillary and syringe are both purchased experimental grade materials. Simply put the capillary on the needle hole of the syringe. Figure 3 shown.

[0031] Example 1

[0032] Core-shell structured Al-loaded calcium-based thermal storage particles

[0033] Based on the preparation process, it is specifically:

[0034] Step 1, the hydrophobic surface component is pure manganese dioxide, which is placed in a culture dish, compacted and tilted;

[0035] Step 2, weigh 12.16g Ca(OH)2 and 2.94g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0036] Step 3, the obtained wet mixture is passed through a capillary and syringe combination tool (such as Figure 3 As shown), calcium-based heat storage particles with uniform particle size are obtained by titrating on a hydrophobic surface;

[0037] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0038] Step 5: The dried particles are calcined at 900° C. for 90 min to obtain the core-shell structure Al-loaded calcium-based heat storage particles, which are labeled as Ca84.5 / Al15.5-Mn1 / C0.

[0039] Example 2

[0040] Core-shell structured Al-loaded calcium-based thermal storage particles

[0041] Based on the preparation process, it is specifically:

[0042] Step 1, the hydrophobic surface components are 20wt% manganese dioxide and 80wt% graphite. At room temperature, manganese dioxide and graphite are stirred at 850r / min to obtain a hydrophobic surface, which is then placed in a culture dish, compacted and tilted;

[0043] Step 2, weigh 12.16g Ca(OH)2 and 2.94g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0044] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain calcium-based heat storage particles with uniform particle size;

[0045] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0046] Step 5: The dried particles are calcined at 900° C. for 90 min to remove the surface graphite, thereby obtaining the core-shell structure Al-loaded calcium-based heat storage particles, which are labeled as Ca84.5 / Al15.5-Mn1 / C4.

[0047] Example 3

[0048] Core-shell structured Al-loaded calcium-based thermal storage particles

[0049] Based on the preparation process, it is specifically:

[0050] Step 1, the hydrophobic surface components are 60wt% manganese dioxide and 40wt% graphite, which are placed in a culture dish, compacted and tilted;

[0051] Step 2, weigh 12.16g Ca(OH)2 and 2.94g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0052] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain calcium-based heat storage particles with uniform particle size;

[0053] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0054] Step 5: The dried particles are calcined at 900° C. for 90 min to remove the surface graphite, thereby obtaining the core-shell structure Al-loaded calcium-based heat storage particles, which are labeled as Ca84.5 / Al15.5-Mn3 / C2.

[0055] Example 4

[0056] Core-shell structured Al-loaded calcium-based thermal storage particles

[0057] Based on the preparation process, it is specifically:

[0058] Step 1, the hydrophobic surface components are 60wt% manganese dioxide and 40wt% graphite, which are placed in a culture dish, compacted and tilted;

[0059] Step 2, weigh 10.16g Ca(OH)2 and 1.14g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0060] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain calcium-based heat storage particles with uniform particle size;

[0061] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0062] Step 5: The dried particles are calcined at 900° C. for 90 min to remove the surface graphite, thereby obtaining the core-shell structure Al-loaded calcium-based heat storage particles, which are labeled as Ca92.5 / Al7.5-Mn3 / C2.

[0063] Example 5

[0064] Core-shell structured Al-loaded calcium-based thermal storage particles

[0065] Based on the preparation process, it is specifically:

[0066] Step 1, the hydrophobic surface components are 60wt% manganese dioxide and 40wt% graphite, which are placed in a culture dish, compacted and tilted;

[0067] Step 2, weigh 9.48g Ca(OH)2 and 3.03g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0068] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain calcium-based heat storage particles with uniform particle size;

[0069] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0070] Step 5: The dried particles are calcined at 900° C. for 90 min to remove the surface graphite, thereby obtaining the core-shell structure Al-loaded calcium-based heat storage particles, which are labeled as Ca80 / Al20-Mn3 / C2.

[0071] Comparative Example 1

[0072] Shell-free core-structured Al-loaded calcium-based thermal storage particles

[0073] Based on the preparation process, it is specifically:

[0074] Step 1, the hydrophobic surface component is pure graphite, which is placed in a culture dish, compacted and tilted;

[0075] Step 2, weigh 12.16g Ca(OH)2 and 2.94g Al(NO3)3 into a beaker, add appropriate amount of deionized water and stir to form a uniform wet mixture;

[0076] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain calcium-based heat storage particles with uniform particle size;

[0077] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0078] Step 5: The dried particles are calcined at 900°C for 90 minutes to remove the surface graphite, thereby obtaining the shell-free core structure Al-loaded calcium-based heat storage particles, which are labeled as Ca84.5 / Al15.5-Mn0 / C1.

[0079] Comparative Example 2

[0080] Core-shell structure calcium-based heat storage particles

[0081] Based on the preparation process, it is specifically:

[0082] Step 1, the hydrophobic surface components are 60wt% manganese dioxide and 40wt% graphite, which are placed in a culture dish, compacted and tilted;

[0083] Step 2, weigh 6g of Ca(OH)2 and put it in a beaker, add an appropriate amount of deionized water and stir to form a uniform wet mixture;

[0084] Step 3, passing the obtained wet mixture through a capillary and syringe combination tool, and titrating on a hydrophobic surface to obtain core-shell structured calcium-based heat storage particles with uniform particle size;

[0085] Step 4, drying the obtained wet granules at 70° C. for 12 h;

[0086] Step 5: The dried particles are calcined at 900° C. for 90 min to remove graphite, thereby obtaining the core-shell structured calcium-based heat storage particles, which are labeled as Ca100-Mn3 / C2.

[0087] Test Example 1

[0088] The light absorption characteristics of the samples of Examples 1-3 and Comparative Example 1 were investigated in the wavelength range of 300-2500 nm using a Carry 5000 Agilent Technologies UV / Vis / NIR spectrometer. About 120 mg of the particle sample was placed in a circular measurement mold and its reflectivity was measured using a spectrometer. In order to quantitatively compare the solar light absorption rates of different samples, the average solar light absorption rate A was introduced. ave The average solar absorptivity is calculated by the weighted integral of the sample absorptivity and the standard solar spectrum AM1.5D. The specific calculation formula is as follows:

[0089]

[0090] Where A(λ) is the solar absorption rate, λ is the wavelength, and I(λ) AM1.5D It is the sunlight spectrum under AM1.5D conditions.

[0091] Under the same Al loading amount, the spectral absorbance of Al-loaded calcium-based thermal storage particles constructed with different hydrophobic surfaces is as follows: Figure 1As shown. The background shaded part is the standard AM1.5D sunlight spectrum corresponding to the right Y-axis. The study found that the spectral irradiation intensity of AM1.5D is mainly concentrated in the wavelength range of 300-1350nm. In the range of 300-1350nm, the average solar absorptivity of Comparative Example 1 is the lowest, which is 19.36%, indicating that the ability of Al-loaded calcium-based heat storage particles without shell core structure to absorb sunlight is poor. The solar absorption capacity of Al-loaded calcium-based heat storage particles with shell core structure gradually increases with the increase of the mass ratio of MnO2 in the hydrophobic surface. The average solar absorptivity is arranged in the following order: Example 1> Example 3> Example 2> Comparative Example 1. The trend of the average solar absorptivity change is consistent with its color depth, among which the absorbance of Example 1 is the highest at 88.72%, which is more than 4.58 times that of Comparative Example 1. However, without adding graphite, the particles have adhesion problems due to the weak hydrophobicity of the hydrophobic surface during granulation; after adding graphite, the strong hydrophobic effect between graphite and water makes the powder adhere better to the surface. The heat storage particles of the present invention are used in a thermochemical energy storage and concentrating heat collection system, which requires the particles to be fluidized to absorb solar radiation. Particle adhesion reduces the sphericity of the particles and is not conducive to the heat conduction of solar radiation absorbed by the black shell on the particle surface to the interior of the particles.

[0092] Test Example 2

[0093] A Jupiter-STA449F5 thermogravimetric analyzer (TGA) was used to perform cyclic energy storage / release experiments on the samples of Examples 3-5 and Comparative Example 2. About 20 mg of the sample was placed in an alumina crucible, and a cyclic storage / release experiment was performed under an alternating atmosphere of CO2 and N2, and 40 storage / release cycles were tested. The sample was calcined at 750°C and 100 ml / min N2 for 15 minutes, and carbonated at 850°C and a mixed atmosphere of 100 ml / min CO2 and 10 ml / min N2 for 15 minutes, with N2 acting as a protective gas. The CO2 absorption capacity per unit mass (C n , gCO2 / g calcined sample) and energy storage density (E g,n , MJ / kg) was used to evaluate the heat storage / release performance of the samples.

[0094]

[0095] Where n is the number of cycles; m car,n and m cal,n They represent the mass of the sample after n times of carbonation and calcination respectively; ΔH is the reaction enthalpy, 178 kJ / mol.

[0096] The calcium-based heat storage particles with different Al-loaded core-shell structures were constructed using 60wt% MnO2 and 40wt% graphite hydrophobic surface. The energy storage density based on CaO in Comparative Example 2 and Examples 3-5 was calculated as follows: Figure 2As shown, all embodiments show relatively stable and reliable thermal energy storage / release capabilities. This is mainly due to the formation of an inert carrier Ca12Al14O33 by doping Al(NO3)3. This skeleton structure enables the heat storage particles to stably store / release heat. However, when the Al doping ratio exceeds a certain value, the energy storage density of the sample calculated based on CaO decreases. After 40 cycles, Example 3 has the highest energy storage density calculated based on CaO, with Eg,n of 1.71 MJ / kg, which is about 1.15 times that of Comparative Example 2.

[0097] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. An Al-loaded core-shell calcium-based heat storage material, characterized in that: It includes a shell formed of manganese and its oxides and a core of a calcium-based material supported by aluminum.

2. The Al-loaded core-shell calcium-based heat storage material according to claim 1, characterized in that: The calcium-based material includes CaO and Ca 12 Al 14 O 33 The content of CaO in the calcium-based material is 92.5%-80%, Ca 12 Al 14 O 33 The content is 7.5%-20%.

3. A method for preparing an Al-loaded core-shell calcium-based heat storage material, characterized in that: The following steps are involved: Step 1, using manganese dioxide and graphite to prepare a hydrophobic surface and placing it at an angle; Step 2, mixing deionized water, calcium hydroxide and aluminum nitrate, and stirring to form a uniform wet mixture; Step 3, the wet mixture obtained in step 2 is titrated on an inclined hydrophobic surface through a capillary and syringe combination tool to obtain wet Al-loaded core-shell calcium-based heat storage particles with uniform particle size; Step 4, drying the wet Al-loaded core-shell structured calcium-based heat storage particles obtained in step 3; Step 5, calcining the particles obtained in step 4 to obtain the Al-loaded core-shell structured calcium-based heat storage particles.

4. The method for preparing an Al-loaded core-shell calcium-based heat storage material according to claim 3, characterized in that: In step 1, the mass ratio of manganese dioxide to graphite is 1:0.6-4.

5. The method for preparing an Al-loaded core-shell calcium-based heat storage material according to claim 4, characterized in that: The mass ratio of the manganese dioxide to the graphite is 3:2, 1:2 or 1:

4.

6. The method for preparing an Al-loaded core-shell calcium-based heat storage material according to claim 3, characterized in that: In step 2, the mass ratio of the calcium hydroxide to aluminum nitrate is 2.5-9:1; the mass volume ratio of the total mass of the calcium hydroxide and aluminum nitrate to deionized water is 3-3.1:

5.

7. The method for preparing an Al-loaded core-shell calcium-based heat storage material according to claim 3, characterized in that: In step 4, the drying temperature is 65-85° C. and the drying time is 12-14 hours.

8. The method for preparing an Al-loaded core-shell calcium-based heat storage material according to claim 3, characterized in that: In step 5, the calcination conditions are: heating to 900° C. at a heating rate of 10° C. / min, and maintaining the constant temperature for 90 min.

Citation Information

Patent Citations

  • Novel material and production thereof for use as a storage medium in a sensitive energy storage system in the low-, medium- or high-temperature range

    CN110366546A

  • Low-cost calcium-based heat storage material and preparation method thereof

    CN113603458A

  • Thermochemical adsorption heat storage material capable of efficiently transferring mass and heat and preparation method thereof

    CN114015418A

  • Preparation method of metal-based phase change heat storage big capsule

    CN115851236A

  • Calcium-based heat storage particles and preparation method thereof

    CN115926758A

Cited By

  • Spherical Li4SiO4-based heat storage material with dark shell and preparation method of spherical Li4SiO4-based heat storage material

    CN121914687A